Ready or not? The anthropometric and physical qualities of youth female rugby league players in England - Briscoe, T.; Darrall-Jones, J.; Heyward, O.; Sawczuk, T.; Jones, B.; Brindle, T.; Barrow, S.; Owen, C.; Heavey, K.; Mackay, L.; Cuthbert, K.; Pinckney, M.; et al. (The Journal of Strength and Conditioning Research, 2026)
This study aimed to quantify the physical and anthropometric characteristics of U13 to U17 youth female rugby league players, compare between age categories, and assess relationships between characteristics. Eighty amateur youth female players completed a testing battery including anthropometric (body mass and height) and physical (strength [isometric mid-thigh pull], peak power [counter movement jump], linear speed [40 m sprint], momentum, and high-intensity intermittent running [HIIR] ability [30-15 Intermittent Fitness Test]) qualities. Progressive increases were found in body mass, peak power, strength, speed, momentum, and HIIR ability with age, between age group differences were nonsignificant. Large significant ( p < 0.01) relationships were found between strength and 10 m ( r = 0.54), 20 m ( r = 0.59), 30 m ( r = 0.59), and 40 m ( r = 0.61) momentum. Body mass showed large significant relationships with all momentum distances (10 m: r = 0.54; 20 m: r = 0.59; 30 m: r = 0.59; 40 m: r = 0.61). A large significant ( p = <0.01) relationship was found between strength and peak propulsive power ( r = 0.59). A moderate negative significant ( p < 0.01) relationship was found between body mass and HIIR ( r = 0.49). This study provides novel age-specific reference values for practitioners to assess strengths and areas of development in youth female rugby league players. Findings highlight the need for tailored strength and conditioning programs to ensure players are physically prepared to transition through the development pathway, with practitioners focusing on improving physical readiness for the demands of senior competition.